Tinjauan Yuridis Terhadap Penolakan Pengosongan Tanah Oleh Pihak Yang Diberi Hak Pakai : Studi Kasus di Desa Numponi, Kecamatan Malaka Timur, Kabupaten Malaka - Yoanita Rostika Lala; Darius Mauritsius; Chatryen M. Dju Bire (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the factors behind the rejection of land vacancy by recipients of land use rights in Numponi Village, East Malaka District, Malacca Regency. Employing an empirical legal research method, the study integrates primary data obtained through interviews and secondary data gathered from literature studies. The data were analyzed using a qualitative descriptive approach. The findings reveal that the refusal to vacate land stems from a combination of internal and external factors. Internal factors include claims made by the right holders over the land, fulfillment of tax obligations, and the perception of ownership by the recipients of use rights. Meanwhile, external factors involve economic interests, cultural values, the influence of a matrilineal customary system that is not yet fully understood by the disputing parties, and a general lack of public awareness regarding agrarian law and the necessity of formal land documentation such as certificates. The study highlights the critical need for better dissemination of agrarian legal knowledge and formal land administration practices within local communities to prevent future disputes and ensure legal certainty over land use rights.